The crows - Fager, Anders, 1964-; Bergting, Peter (Dark Horse Books, 2022)
After Kim inherits an old family house in rural Sweden, he finds strange notes and drawings posted everywhere, soon seeing monsters and ruminating on his family, himself, and the traumatic memories of his upbringing.